Project management essentials : a quick and easy guide to the most important concepts and best practices for managing your projects right - Athayde, William P. (Maven House Press, 2013)
If you are new to project management or need to refresh your knowledge, this book will help you learn how to manage projects successfully. The concepts presented are not rocket science. They are just common sense. Read the book and discover the key skills and knowledge you'll need to be an effective project manager including guidelines for building a usable project plan; strategies to deal with conflict, change, uncertainty, and risk; and how to report on the progress of the project and keep everyone concerned happy. The book is purposefully written in short, clear chapters to make project management more easily understood. The authors bring both their business experience and their academic backgrounds to make these chapters come alive.